Mejoramiento de frijoles volubles para sistemas de siembra de asociacion con maiz - Davis, J.H.C. (International Center for Tropical Agriculture, 1978)
Maize and climbing beans are traditionally planted in association in the sierra regions of L.A. with alt. higher than 1500 m. The system has shown a series of advantages: low incidence of certain pests and diseases, less root lodging in maize, and less risk for the farmers. The types of climbing bean and maize used in associated cropping systems were studied. In general, maize and bean yields were negatively related and it was found that yields of tall maize genotypes were less affected by beans than short maize genotypes. Root lodging of tall maize genotypes was notably reduced in association. Stem lodging of short maize genotypes was due to the vigorous growth of some climbing bean var. Very vigorous bean var. could not reach their own yield potential with short maize genotypes due to the poor support system. In yield trials with climbing bean breeding material, both relay and associated cropping systems with maize had lower costs than beans in monoculture as well as being the most representative system used by farmers. Yields of bean genotypes in association were generaly lower and had less significant differences than in monoculture. It was concluded that with an appropriate management of plot size and border effects, climbing bean yields were higher in association and were favorably assessed from an economic standpoint. (AS-CIAT)